Nanofabricated Racks of Aligned and Anchored DNA Substrates for Single-Molecule Imaging - Gorman, Jason (American Chemical Society, 2009)
[Image: see text] Single-molecule studies of biological macromolecules can benefit from new experimental platforms that facilitate experimental design and data acquisition. Here we develop new strategies to construct curtains of DNA in which the molecules are aligned with respect to one another and maintained in an extended configuration by anchoring both ends of the DNA to the surface of a microfluidic sample chamber that is otherwise coated with an inert lipid bilayer. This “double-tethered” DNA substrate configuration is established through the use of nanofabricated rack patterns comprised of two distinct functional elements: linear barriers to lipid diffusion that align DNA molecules anchored by one end to the bilayer and antibody-coated pentagons that provide immobile anchor points for the opposite ends of the DNA. These devices enable the alignment and anchoring of thousands of individual DNA molecules, which can then be visualized using total internal reflection fluorescence microscopy under conditions that do not require continuous application of buffer flow to stretch the DNA. This unique strategy offers the potential for studying protein−DNA interactions on large DNA substrates without compromising measurements through application of hydrodynamic force. We provide a proof-of-principle demonstration that double-tethered DNA curtains made with nanofabricated rack patterns can be used in a one-dimensional diffusion assay that monitors the motion of quantum dot-tagged proteins along DNA.